Acoustic Influence of Vehicles on a Protected Natural Area in the Southwest of the Iberian Peninsula - SÁNCHEZ-SÁNCHEZ, Rafael; FORTES-GARRIDO, Juan Carlos; BOLIVAR, Juan Pedro (Archives of Acoustics, 2018)
Natural sounds are essential elements for ecosystems, and therefore necessary for many ecological functions, forming what is called “natural soundscapes”. The Natural Reserve Laguna del Portil (NRLP), located in the southwest of the Iberian Peninsula, is an ecosystem which was declared by Spanish authorities as Protected Natural Reserve. In the south area of the NRLP, there is a regional road with high traffic intensity, which affects the soundscapes of this natural reserve. In this study, the road potential noise impact on the natural sounds of the NLRP is analysed. This analysis was done both in winter and summer, and also using two independent methods: 1) spatial sampling measures in 43 different points of the NRL; and 2) noise mapping using noise levels prediction software. From the comparison of the results of both methods and seasons the following conclusions were reached: 1) an approach to the natural soundscape of NRLP both in winter and summer, 2) the acoustic impact of the road on the NRLP, and 3) the variation of the traffic noise depending on the distance to the road, and its seasonal variation. This study could be to improve the management of the NRLP and to help to preserve the natural soundscape of the reserve.